Глобалізація та її вплив на міжнародні економічні відносини. - Антипенко, Надія Василівна; Antypenko, Nadiia; Почерніна, Наталя Вікторівна; Pochernina, Nataliia; Васильківський, Дмитро Миколайович; Vasylkivskyi, Dmytro (My University, 2024)
UKR: У дослідженні було розкрито основні підходи до визначення поняття «глобалізація», що існують в укра їнській та міжнародній науковій думці. Визначено ключові прояви та основні риси глобалізації, а також пе редумови, що визначають цей процес. Охарактеризовано позицію України поміж країн світу стосовно рівня глобалізації за допомогою індексу KOF Globalisation Index. Описано тенденцію зміни значень цього індексу за період незалежності України. Деталізовано сутність індексу глобалізації для України через характеристику його субіндексів: індексів соціальної, економічної та політичної глобалізації. Зауважено тенденції до посилен ня процесів регіоналізації та деглобалізації, виявлено їх вплив на міжнародні економічні відносини в цілому та в Україні. За результатами проведеного аналізу визначено переваги та недоліки сучасних глобальних про цесів для національної економіки.

ENG:The relevance of the research topic is determined by the heterogeneity of scientists' approaches to determining its advantages and modern challenges. In particular, along with a number of advantages of globalization, the main one of which is the expansion of opportunities for national economies, there are problems related to the uneven distribution of benefits for countries depending on their level of development, increasing dependence of developing countries on developed countries. These and other reasons led to the intensification of the scientific discourse regarding the processes of regionalization and deglobalization, the trends of which are intensifying recently. Considering the above-mentioned aspects, it is important for Ukraine to balance the national economic policy with the international one, first of all, preserving national priorities. The purpose of the work is to assess the impact of modern globalization trends on international economic relations as a whole and in the context of Ukraine. During the research, methods of analysis and synthesis, statistical method, rating method were used. As a result of the analysis, the main approaches to defining the concept of "globalization" that exist in Ukrainian and international scientific periodicals were revealed. The key manifestations and main features of globalization are defined, as well as the prerequisites that determine the modern qualities of globalization. The position of Ukraine among the countries of the world in relation to globalization is characterized using the KOF Globalization Index. The trend of changes in the values of this index during the period of Ukraine's independence is described. The essence of the globalization index for Ukraine is detailed through the characteristics of its sub-indices – indices of social, economic and political globalization. Tendencies to strengthen the processes of regionalization and deglobalization are noted and their impact on international economic relations as a whole and in Ukraine is revealed. Based on the results of the analysis, the advantages and disadvantages of modern global processes for the economy of Ukraine were determined. The practical value of the research results lies in identifying the impact of the processes of globalization, regionalization and deglobalization on international relations with the identification of the main advantages and disadvantages for developing countries (using the example of Ukraine), which can be useful for adapting national economic policies to modern globalization trends.
Globalization and its impact on international economic relations.
Keywords: глобалізація; міжнародні економічні відносини; міжнародні економічні відносини; KOF Globalisation Index; регіоналізація; деглобалізація; globalization; international economic relations; international economic relations; KOF Globalization Index; regionalization; globalization